Sistem Kendali Multi Point Berbasis Telegram - Jabbar, A. Abd.; Said, Muh. (Jurnal Sintaks Logika, 2025)
This research focuses on energy-saving solutions through IoT-based smart homes. Telegram-based multi-point control system is designed to optimize the use of electronic devices. The purpose of this research is to design and develop a Telegram-based on/off multi-point control system on automatic lights to optimize the use of electronic devices, improve energy efficiency, and adapt to technological developments and modern lifestyle needs. The method used in this study is qualitative based on RND, which aims to develop and test new or improved products with a focus on numerical measurements. The test results were analyzed to assess the performance of the system in responding to commands at various distances and conditions, both with and without obstacles.